Green financing and its role in improving the performance of green banks : - An analytical survey of the views of a sample of bank managers - Zainab Makki Albanaa; Nour Nabil Abdel Amir (Iraqi Journal for Administrative Sciences, 2024)
The purpose of the research is to measure and analyze the extent of banks' adoption of green financing strategies and to indicate the extent of the impact of green financing in improving the performance of green banks as one of the modern approaches in banking. To achieve the objective of the research, a randomly selected sample from a number of five Iraqi banks, And its formulation through the study of previous studies and arbitration by a number of professors who have competence and distributed to the top management in the banks sample research by (10) form for each bank was analyzed and draw conclusions and findings, the most important lack of clear understanding of the Financing green mussels and green banks being a new concept. A number of recommendations have been proposed. The most important of these recommendations is to urge the Central Bank to prepare the supervisory instructions for Iraqi banks in a manner that requires them to take into account the objectives of sustainable development and green banking in the practice of various banking activities.